If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -9(5 + -1x) = 0 9 + (5 * -9 + -1x * -9) = 0 9 + (-45 + 9x) = 0 Combine like terms: 9 + -45 = -36 -36 + 9x = 0 Solving -36 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 9x = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 9x = 0 + 36 9x = 0 + 36 Combine like terms: 0 + 36 = 36 9x = 36 Divide each side by '9'. x = 4 Simplifying x = 4
| 23+5=123455666780000 | | 23+5= | | 4t=2t-1 | | 1/2k+1=0.7 | | t/6-3=12 | | 62.8+x=180 | | 2y-8y+5y-6y= | | 3+91x=52x+27 | | 24x^2=30x | | 6t=3t-4 | | 12t=5t-9 | | 32-5x=2 | | -36=-12(-9-3x) | | u+5(u-5)=6(u-6) | | (3a-3)(4a+5)=0 | | (2x+9)(2x+21)=425 | | 19x-y-8=0 | | x/3-4/9x | | f(x)=x^2+32 | | (5u+9)(5-u)=0 | | 2.6+10m=6.91 | | -5/4h=11-9/4h | | 4f=10+3f | | 11.3e=12.8+7.5e+35.6 | | (3x-5)(x+6)(4x+7)=0 | | 4(3x-5)(6x+5)=0 | | 80x*x=10 | | 10x*8x=10 | | 1.42g-9=0.23 | | 4b^2-31b-90=0 | | 5d-d-2d+-8-3d=0 | | 6(x-3)=4(x+9)-20 |